2009
DOI: 10.5424/sjar/2009073-444
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation of Autumn and Spring-sown vetch (Vicia sativa ssp.) populations in central Turkey

Abstract: In central Turkey, common vetch (Vicia sativa ssp. sativa) is traditionally grown in spring. Frequent droughts cause crop failures. Autumn sowing can give higher yields, but then winter plant death is a major problem. The objective of this research was to explore and quantify variation available in V. sativa ssp. germplasm for winter hardiness, yield and adaptability. Eleven plant characters were evaluated in 164 vetch populations in autumn and spring sowings over two years, and their inter-relationships were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The data were expressed as weight in g per 1,000 seeds. Common vetch genotypes were arbitrarily grouped for seed size based on the 1,000-seed weight as large (≥51 g), medium (36 to 50 g), and small (≤35 g) as applied by Firincioglu et al [17].…”
Section: Plant Materialsmentioning
confidence: 99%
“…The data were expressed as weight in g per 1,000 seeds. Common vetch genotypes were arbitrarily grouped for seed size based on the 1,000-seed weight as large (≥51 g), medium (36 to 50 g), and small (≤35 g) as applied by Firincioglu et al [17].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Similar results were obtained in the trials with common vetch in Syria, where high grain yield was strongly correlated with harvest index (Abd El-Moneim, 1993). In addition, in numerous trials in various regions of Turkey, it was also found that grain yield was significantly and positively correlated to both number of pods per plant and number of grain per plant (Cakmakci et al 2006;Fırıncıoğlu et al 2009). This points out the significance of the role these two yield components may play in developing the common vetch cultivars with high and stable grain yield (Blum and Lehrer, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…sativa) is one of the most important annual forage legumes in the world because of its multiple uses (i.e. hay, grain, straw, silage and green manure), its high nutritional value, and its ability to grow over a wide range of climatic and soil conditions (Fırıncıoğlu et al, 2009;Jong et al, 2013). Hairy vetch (Vicia villosa Roth.)…”
Section: Introductionmentioning
confidence: 99%
“…Because winter damage and death of vetch is a major problem in central Turkey, V. sativa is sown in spring, although Fırıncıoğlu et al . (,b, ) have recently reported some cold‐tolerant lines of V . sativa L. developed for autumn planting.…”
Section: Introductionmentioning
confidence: 99%
“…Vetches ( Vicia spp.) are widely grown for forage and grain in the Mediterranean basin, Eastern Europe, the former Soviet Union and Turkey (Francis et al ., ; Firincioğlu et al ., , ). The genus contains about 150 species of annual and perennial herbs and numerous cultivars and landraces (Alinoğlu and Durlu, ).…”
Section: Introductionmentioning
confidence: 99%